Development and Expert Validation of a Web-Based Learning Medium for Computer Components in Junior High School Informatics Education - Dinda Amelia Putri Lubis; Samsidar Tanjung; Sri Yunita (CV. Media Inti Teknologi, 2026)
Background: The integration of digital technology in education drives the development of innovative learning media to enhance students' conceptual understanding. However, Informatics instruction on computer components for seventh-grade students at SMP Riad Madani still relies heavily on conventional textbooks and teacher-centered approaches, limiting interactive and independent learning. Therefore, technology-based learning media aligned with curriculum goals are needed.Aims: This study aimed to develop and evaluate the feasibility of a web-based learning medium for teaching computer components to seventh-grade Informatics students at SMP Riad Madani.Methods: This study employed a research and development (R&D) approach using a modified ADDIE framework (Analysis, Design, Development, and Evaluation). Product feasibility was evaluated by six experts: two subject-matter experts, two media experts, and two instructional design experts. Data collected via validation instruments were analyzed using descriptive percentage statistics.Results: Expert validations demonstrated high product feasibility. Instructional design experts assigned an average score of 98.8%, followed by media experts at 80.2%, and subject-matter experts at 82.3%. The overall feasibility score of 87.1% indicates the product meets established standards for content quality, instructional design, functionality, and usability.Conclusion: The developed web-based learning medium is highly feasible for supporting Informatics instruction. These findings provide a solid basis for future classroom implementation and effectiveness studies.